Synthesis of Novel Fluorescent Carbon Quantum Dots From Rosa roxburghii for Rapid and Highly Selective Detection of o-nitrophenol and Cellular Imaging - Zhang, Qianchun; Liang, Junyi; Zhao, Li; Wang, Yan; Zheng, Yuguo; Wu, Yun; Jiang, Li (Frontiers in Chemistry, 2020)
A novel carbon quantum dots (CQDs) were successfully synthesized by one-step hydrothermal reaction using Rosa roxburghii as a biomass-based precursor. The CQDs have an average size of 2.5 nm and a narrow size distribution. They display strong blue fluorescence with a quantum yield of 24.8% and good biocompatibility. Notably, these CQDs were capable of detecting trace o-nitrophenol in surface water and sewage with high sensitivity and specificity. The linear range is 0.08 to 40 μmol/L, and the limit of detection is 15.2 nmol/L. Furthermore, this CQDs was successfully applied for o-nitrophenol analysis in river water and sewage samples. Additionally, Hep3B cells, a human hepatocellular carcinoma cell line, can be easily imaged with high resolution using the as-prepared CQDs as nanoprobes. These results reveal that the as-prepared CQDs have potential applications for detecting o-nitrophenol and cell imaging.